HERD IMMUNITY (KEKEBALAN KELOMPOK) DALAM PEMBERIAN IMUNISASI VAKSIN COVID-19 DI WILAYAH KERJA PUSKESMAS GUGUK PANJANG KELURAHAN AUR KUNING BUKITTINGGI - Mera Delima; Andrye Fernandes; Yendrizal Jafri; Yessi Andriani; Rinawati Kasrin (COVIT (Community Service of Health), 2022)
In Indonesia, the target of herd immunity/(herd immunity) is 70% in accordance with the characteristics of the spread of Covid-19. The development and discovery of the Covid-19 vaccine as well as minimal public compliance raises the issue of "herd immunity. The purpose of this community service is to increase public knowledge about the delivery of the COVID-19 vaccine. From the field survey data, it was found that 88% of the residents of Aur Kuning Village on average had a bad attitude about PHBS in the New Normal Era, and were not willing to be vaccinated to prevent Covid-19 transmission. Furthermore, observation and interview data for three families (Heads of Families) in the Aur Kuning sub-district also knowledge about the Covid-19 vaccine is still not good, people think that vaccines are not effective in preventing the transmission of Covid 19, and there is no information regarding the Covid-19 vaccine given to them. Public. This made the community service team interested in providing an explanation about Herd Immunity (herd immunity) in administering the Covid-19 vaccine and also the head of the village at that time asked the Community Service Team of the Perintis Indonesia University to provide counseling about administering the Covid-19 vaccine in the Guguk Panjang Health Center Work Area. Aur Kuning Village, Bukittinggi. The method used in this service is to provide counseling about the importance of the Covid-19 vaccine by means of lectures, discussions, and questions and answers. The results of this activity obtained that the majority of participants were aged around 30 to 60 years, the majority of which were high school education. After conducting health education about the Covid-19 vaccine, there was an increase in public knowledge about the importance of the Covid-19 vaccine. It is recommended that after this service the community is willing to carry out the Covid-19 vaccine and still pay attention to health protocols Keywords: Herd Immunity, Covid-19 vaccine